Mineral phases in iron ore sinters produced with oak sawdust substitute fuel - Mežibrický R.; Fröhlichová M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this paper, the effect of oak sawdust – a cheap substitute fuel on the quality of sinter in terms of its phase composition is evaluated. The samples of sinters prepared with 5, 9, and 13% equivalent fixed carbon substitution of coke breeze by oak sawdust were analyzed by light microscopy, SEM-EDS and powder XRD analysis. The microstructure of sinters in places with fuel residues consisted of well-integrated secondary mineral phases, confirming good conditions for sintering. The phase analysis has shown a predominance of low-Fe SFCA modification over the high-Fe SFCA-I and the increasing trend in the ratio of magnetite with an increasing degree of fuel substitution up to 8%. As a conclusion, the sinters made with a partial replacement of fuel are in terms of the total phase composition comparable to sinter fueled with coke only and therefore qualitatively satisfactory for blast furnace process.